Some observations on tourism developments in a peripheral region and the validity of global value chain theory. The Anti-Atlas Mountains in Morocco - Popp, Herbert; El Fasskaoui, Brahim (ERDKUNDE, 2013)
This paper has two different yet complementary aims. The first section, based on comprehensive empirical analysis and descriptive research, portrays a region that has yet to be much affected by tourism in terms of what can be observed so far and its potential. This research, which is contained in a detailed tourist map of the western Anti-Atlas (included in this contribution), is an attempt to systematically collect information on the region that is relevant for tourism. The cartography itself was not based on an explicit theory; instead, it is the synthesis of many years of experience visiting the area. The map is designed to provide assistance to tourists travelling to the Anti-Atlas, i.e., it is intended for practical purposes. In the second part of this contribution, some of the results from the empirical research are examined in terms of their correspondence with global value chain theory, and the validity of theoretical hypotheses is tested against the empirical results. In the first part of the paper, the western Anti-Atlas is introduced as a region with considerable tourism potential that has yet to see much development. The region’s features that are relevant for cultural and heritage tourism (natural and cultural heritage sites) are described and mapped on the basis of the authors’ own research and visits. Transport infrastructure and accommodation are also incorporated fully into the map, again based on the authors’ own visits and interviews with local actors. The reasons that tourism has seen little development are presented, and it is observed that the international visitors encountered in the region differ from the classical type of package tourist in many ways. Thereafter, the validity of global value chain theory is assessed in the region. Recent theoretical approaches have demonstrated that international tourism even in peripheral regions of so-called “developing countries” follows the principles of global value chains. These state that travel operators in Europe, North America, Japan and Australia dominate and control tourism, and that local actors in the destination country are unable to break out of this grip with alternative strategies. This paper takes as its starting point the observation that the dependency observed and empirically confirmed elsewhere in fact hardly exists in the Anti-Atlas, and that other factors are at work. The results of our empirical research are used to test the validity of global value chain theory (and to refute its global validity). Finally, the region is characterised as a tourism destination in which global value chains have apparently been broken, with tourists booking tourism products directly with (accommodation) providers in the region.